WaterWiSe@SG : a testbed for continuous monitoring of the water distribution system in Singapore - Whittle, Andrew J. (2013)
This paper describes the development of WaterWiSe@ SG, a wireless sensor network to enable real-time monitoring of a water distribution network in Singapore. The overall project is directed towards three main goals: 1) the application of a low cost wireless sensor network for high data rate, on-line monitoring of hydraulic parameters within a large urban water distribution system; 2) the development of systems to enable remote detection of leaks and prediction of pipe burst events; 3) the integrated monitoring of hydraulic and water quality parameters. In this paper we will describe the current state of the WaterWiSe@SG testbed, and report on experimentation we have performed with respect to leak detection and localization. Furthermore, we describe how we have assimilated real time pressure and flow measurements from the sensor network into hydraulic models that are used to improve state estimation for the network. Finally, we discuss the future plans for the project.